Calpain inhibition by calpeptin does not prevent APLT activity reduction in PS-exposing platelets, but calpeptin has independent pro-apoptotic effects - Gwozdz, Adam M.; Leung, Roland; Wang, Hong; Bang, K. W. Annie; Packham, Marian A.; Freedman, John; Rand, Margaret L. (Thrombosis and Haemostasis, 2010)
Exposure of procoagulant phosphatidylserine (PS) on the surface of activated platelets is not readily reversible and this may propagate thrombosis. Persistence of PS exposure may be attributed, at least in part, to a continued reduction of the activity of aminophospholipid translocase (APLT), that transports PS from the outer to the inner membrane leaflet. We investigated whether calpain is involved in the inhibition of APLT activity. In flow cytometric investigations, using the inhibitors calpeptin or E64d at a concentration that blocks calpain activation, we found that calpain is not responsible for the reduction in APLT activity that results in persistence of PS exposure. Unexpectedly, we found that the inhibitors had additional effects independent of blocking calpain. Incubation of resting platelets with calpeptin resulted in a subpopulation of platelets with increased intracellular Ca2+ and persistent PS exposure. The inhibitors also increased the proportion of platelets with persistent PS exposure in suspensions stimulated with thrombin and/or collagen or the Ca2+-ionophore A23187 under conditions in which calpain was not activated or in which its activation was completely blocked; P-selectin expression on thrombin and/ or collagen-stimulated platelets was inhibited. Furthermore, in stimulated platelets, calpeptin increased the proportion of the PS-exposing platelets expressing a second apoptotic hallmark, collapsed mitochondrial inner membrane potential (ΔΨm). These additional effects of calpeptin on platelet regulation of intracellular Ca2+ levels and apoptotic-like events should be taken into account when it is used as an inhibitor of calpain.
Keywords: Calpain; calpeptin; PS expression; apoptosis; aminophospholipid translocase